Effects of cilostamide and forskolin on the meiotic resumption and embryonic development of immature human oocytes - Shu, Yi-min; Zeng, Hai-tao; Ren, Zi; Zhuang, Guang-lun; Liang, Xiao-yan; Shen, Hong-wei; Yao, Shu-zhong; Ke, Pei-qi; Wang, Ning-ning (Human reproduction (Oxford), 2008)
BACKGROUND In an attempt to allow for acquisition of oocyte cytoplasmic maturation, PDE3 specific inhibitor, cilostamide and adenylate cyclase activator, forskolin were used to extend pre-maturation culture of immature human oocytes. METHODS Cumulus–oocyte complexes retrieved from unstimulated ovaries were continuously cultured under 20 µM cilostamide or 50 µM forskolin, alone or in combination for 6, 12, 24 or 48 h, respectively. Levels of intercellular gap junction communication (GJC) and maturational status were examined at these designated time points. Metaphase II oocytes obtained following 54 h biphasic culture (with meiotic inhibitors from 0 to 24 h, no meiotic inhibitors from 24 to 54 h) were subject to intracytoplasmic sperm injection and embryos were cultured for five more days. RESULTS Both cilostamide and forskolin delayed spontaneous meiotic progression after continuous culture with immature human oocytes. Combined treatment of cilostamide and forskolin significantly lowered the rates of germinal vesicle breakdown (GVBD) at 6, 12, 24 or 48 h after meiotic inhibitory culture, when compared with the control (all P < 0.05). A delay of 6 h for the loss of GJC was also observed under the combined treatment of cilostamide and forskolin. The fertilization rate was significantly higher under the combined treatment of cilostamide and forskolin than that of the control. Although the rates of oocyte maturation and embryo cleavage were similar among groups, there was a slight but non-significant increase in blastocyst formation rate with the treatment of cilostamide and forskolin. CONCLUSIONS Combined treatment of cilostamide and forskolin positively influences oocyte developmental competence by exhibiting a synergistic effect on the prevention of GJC loss and resumption of meiosis.